In vitro efficacy of Er:YAG laser-activated irrigation versus passive ultrasonic irrigation and sonic-powered irrigation for treating multispecies biofilms in artificial grooves and dentinal tubules: an SEM and CLSM study - Pingping Bao; He Liu; Lan Yang; Lulu Zhang; Liwei Yang; Nannan Xiao; Jing Shen; Jiayin Deng; Ya Shen (BMC, 2024)
Abstract Background Multispecies biofilms located in the anatomical intricacies of the root canal system remain the greatest challenge in root canal disinfection. The efficacy of Er:YAG laser-activated irrigation techniques for treating multispecies biofilms in these hard-to-reach areas has not been proved. The objective of this laboratory study was to evaluate the effectiveness of two Er:YAG laser-activated irrigation techniques, namely, photon-induced photoacoustic streaming (PIPS) and shock wave-enhanced emission photoacoustic streaming (SWEEPS), in treating multispecies biofilms within apical artificial grooves and dentinal tubules, in comparison with conventional needle irrigation (CNI), passive ultrasonic irrigation (PUI), and sonic-powered irrigation (EDDY). Two types of multispecies root canal biofilm models were established in combination with two assessment methods using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) with the aim to obtain more meaningful results. Methods Ninety extracted human single-rooted premolars were chosen for two multispecies biofilm models. Each tooth was longitudinally split into two halves. In the first model, a deep narrow groove was created in the apical segment of the canal wall. After cultivating a mixed bacterial biofilm for 4 weeks, the split halves were reassembled and subjected to five irrigation techniques: CNI, PUI, EDD, PIPS, and SWEEPS. The residual biofilms inside and outside the groove in Model 1 were analyzed using SEM. For Model 2, the specimens were split longitudinally once more to evaluate the percentage of killed bacteria in the dentinal tubules across different canal sections (apical, middle, and coronal thirds) using CLSM. One-way analysis of variance and post hoc multiple comparisons were used to assess the antibiofilm efficacy of the 5 irrigation techniques. Results Robust biofilm growth was observed in all negative controls after 4 weeks. In Model 1, within each group, significantly fewer bacteria remained outside the groove than inside the groove (P < 0.05). SWEEPS, PIPS and EDDY had significantly greater biofilm removal efficacy than CNI and PUI, both from the outside and inside the groove (P < 0.05). Although SWEEPS was more effective than both PIPS and EDDY at removing biofilms inside the groove (P < 0.05), there were no significant differences among these methods outside the groove (P > 0.05). In Model 2, SWEEPS and EDDY exhibited superior bacterial killing efficacy within the dentinal tubules, followed by PIPS, PUI, and CNI (P < 0.05). Conclusion Er:YAG laser-activated irrigation techniques, along with EDDY, demonstrated significant antibiofilm efficacy in apical artificial grooves and dentinal tubules, areas that are typically challenging to access.